Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1128/mra.01000-19
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Kosakonia radicincitans UYSO10, an Endophytic Plant Growth-Promoting Bacterium of Sugarcane ( Saccharum officinarum )

Abstract: Kosakonia radicincitas UYSO10 is an endophytic bacterium that was isolated from stem tissues of Saccharum officinarum plants cultivated in Uruguay. UYSO10 is a diazotrophic indoleacetic acid-producing bacterium with growth-promoting effects on sugarcane. Here, we report the draft genome sequence, in which genes that are probably involved in the plant-bacterium interaction were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
(15 reference statements)
0
4
0
1
Order By: Relevance
“…When detected, PBC6.1 colonized to ~2×10 5 CFU g –1 of root FW. Kosakonia sacchari is known to be associated with sugarcane ( Saccharum officinarum ) ( Chen et al , 2014 ; Gu et al , 2014 ) and sweet potato ( Ipomoea batatas ) ( Shinjo et al , 2016 ), while other members of the genus Kosakonia (formerly part of Enterobacter ) are beneficially associated with cereal crops including wheat ( Kämpfer et al ., 2005 ), sugarcane ( Taule et al , 2016 ; Beracochea et al , 2019 ; Taule et al , 2019 ), rice ( Oryza sativa ) ( Li et al , 2016 ; Li et al , 2017 ), and corn ( Kämpfer et al ., 2016 ). Using fluorescence microscopy of roots inoculated with a strain of PBC6.1 expressing RFP, we observed colonization of the corn root surface along the perimeters of cells ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When detected, PBC6.1 colonized to ~2×10 5 CFU g –1 of root FW. Kosakonia sacchari is known to be associated with sugarcane ( Saccharum officinarum ) ( Chen et al , 2014 ; Gu et al , 2014 ) and sweet potato ( Ipomoea batatas ) ( Shinjo et al , 2016 ), while other members of the genus Kosakonia (formerly part of Enterobacter ) are beneficially associated with cereal crops including wheat ( Kämpfer et al ., 2005 ), sugarcane ( Taule et al , 2016 ; Beracochea et al , 2019 ; Taule et al , 2019 ), rice ( Oryza sativa ) ( Li et al , 2016 ; Li et al , 2017 ), and corn ( Kämpfer et al ., 2016 ). Using fluorescence microscopy of roots inoculated with a strain of PBC6.1 expressing RFP, we observed colonization of the corn root surface along the perimeters of cells ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…N metabolism. Although the strain UYSO10 is diazotrophic, and the genome encodes for two nitrogenases (Beracochea et al 2019), the enzymes were not detected, probably due to the presence of oxygen in both conditions evaluated (de Bruijn 2015). Interestingly, the downregulation of speci c proteins related to the uptake of different N-sources was observed in the presence of root exudates.…”
Section: Nutrient Transport and Metabolismmentioning
confidence: 99%
“…Subsequently, the genome was sequenced, analyzed, and the strain was de ned as belonging to the species Kosakonia radicincitans (Beracochea et al 2019). In silico genome analysis showed the presence of two nitrogenase-encoding operons, Mo-and Fe-nitrogenase (Beracochea et al 2019). Simple and double mutants in the nitrogenase structural nifH and anfH genes were constructed, and their in vitro characterization showed that both enzymes were active.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A versatilidade desta espécie endofítica na fixação biológica de nitrogênio e sua habilidade única em colonizar seus hospedeiros, tem sido utilizada para composição de bioinoculantes [377][378][379] . As formulações contendo cepas desta espécie foram responsáveis pelo aumento da produção de pepino, tomate, milho e cana de açúcar, destacando seu impacto positivo em diferentes culturas agrícolas 255,256,380,381 . Apesar da cepa K. radicincitans UMEnt01/12 ter sido isolada de tecidos de banana sintomáticos para a doença da murcha bacteriana 382 , não há evidências de efeitos fitotóxicos desta espécie para as plantas, o que foi observado nos nossos screenings.…”
Section: Minimização Do Efeito Do Dióxido De Carbono Na Promoção Do C...unclassified